BANKLARNING BANKLARARO HISOB-KITOBLARNI AMALGA OSHIRISHI - Olimjonov Hamidillo Murodjon o'g'li,; Olimjonov Hamidillo Murodjon o'g'li, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article analyzes the process by which banks carry out interbank settlements. The study is aimed at studying the essence, significance and key elements of the system of interbank settlements. The article covers the principles of functioning of the system of interbank settlements, forms of settlements and their advantages and disadvantages. Also, on the basis of international experience, directions for improving the system of interbank settlements in Uzbekistan have been proposed.